Validity of Physics Module Development in Electronics Subject Project-Based Operational Amplifier Material - Nehru Nehru; Febri Berthalita Pujaningsih; Beta Olivia Arunde (Universitas Lambung Mangkurat, 2024)
This study aims to develop teaching materials in physics learning modules in project-based operational amplifier material electronics courses that are valid for use. This type of research is development research with a research and development method and a 4-D development model that includes four stages: define, design, develop, and disseminate. However, this research is limited to the development stage. The test subjects in this study were two validators, material expert validators and media experts. The data collection instrument is a validated questionnaire. The results of the questionnaire obtained from this development research are as follows: (1) The validity of the physics module in the project-based operational amplifier material electronics course is declared very valid with a percentage of (85%) in terms of material aspects. (2) The validity of the physics module in the project-based operational amplifier material electronics course is declared very valid, with a percentage value of 86% in terms of media aspects. So, it can be concluded that the physics learning module in the project-based operational amplifier material electronics course is valid for use as teaching material. This study implies that the module developed can serve as a supplement to educational activities.